THE INTERACTION OF HINDUISM-ISLAMIC COMMUNITY IN DUSUN BATU GAMBIR DESA PAKRAMAN JULAH BULELENG REGENCY - I Nengah Lestawi (Center for Research and Development of Religious Literature and Heritage, 2017)
Globalization that is sweeping the globe makes Balinese human relationships can not be confined within a narrow community atmosphere, such as; sectarian, tribal, race and religion. However, a Balinese human relationship has grown rapidly among the community which then penetrate the walls of bounds such as class, ethnicity, race and religion. Balinese society generally had been conscious to keep the Balinese suatainability, where the Balinese people want to go back to their own identity, so that various cultural values are revitalized, because some have been mixed and melted with foreign cultural values. It can be shown from nature and Balinese human character in the perspective of Balinese human which is meaningful individually or collectively. The style of the Balinese social community, genersally the social-religious one within a Desa Pakramanis having very thick characteristics according to the category of the values & characters above. Balinese culture is rooted in the Hindu religion that full of tolerance and high solidarity. In addition, Hinduism is a religion that is universal which implementation in various places in Bali is different. However, the core essences of the teachings remain the same